The implementation of warehouse management system at small and medium sized entreprises - Khoffi, Malek (2021)
A combination of research methodology approaches has been employed in this paper. This includes a theoretical framework that elaborates the problem identification and the existing supply chain process for introducing an automated Warehouse Management System, followed by a detailed literature review regarding the complemented supply chain software and hardware to ensure the success of the new architecture within the warehouse. The work project involves the critical success factors as well as the key challenges towards a smart Warehouse Management System. A practical application of a Tunisian medium-sized textile company illustrates the logistics dynamics after integrating the new management process.